Asymmetric effect of monetary policy on Indian stock market sectors: Do monetary policy stimulus transpire the same effect on all sectors? - Kunwar Sanjay Tomar; Subodh Kesharwani (Cogent Economics & Finance, 2022)
Most studies for the monetary policy effect on stock markets have concentrated on using the primary index to proxy the stock market. The present paper, avoiding 'aggregation bias', seeks to unbundle the effect of monetary policy on the stock market in two ways. First, the non-linear model is used. Second, sector-level monetary policy variable association and strength is known. Nonlinear Auto-Regressive Distributed Lag method (NARDL) has been used to separate the effect of monetary policy implications. The positive and negative separation of monetary policy variables shows meaningful information relating to each sector. Furthermore, the NARDL model provides the Error Correction equation for future prediction of the sector performance. The Error Correction Term (ECT) is significant for all the sectors, besides Information Technology. While ECT is highest for the Power sector, the lowest is reported for the Metal sector. Inflation increase has substantially more effect on sectors then its decrease. For short-run, real exchange rate positive (REER_POS (-2)), with a lag of 2 months, is effective for all the sectors. The health care sector stands out in its sensitivity to monetary policy variables. The asymmetric response of the Sector equity markets to monetary policy variables throws new insight for the policymakers, business managers, and fund managers. The nonlinearity can be helpful for business managers to relate revenue and valuation to monetary policy. Likewise, the portfolio fund managers can prepare for the expected changes in the economy to reallocate and rebalance their portfolios.
Keywords: 330; Non-linear Model; monetary policy asymmetric effectiveness; sectoral stock market; Bombay stock exchange India